2023
DOI: 10.1001/jamanetworkopen.2023.10332
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Health Care Professionals’ Choice to Practice in Rural Minnesota

Abstract: ImportanceRural health inequities are due in part to a shortage of health care professionals in these areas.ObjectiveTo determine the factors associated with health care professionals’ decisions about where to practice.Design, Setting, and ParticipantsThis prospective, cross-sectional survey study of health care professionals in Minnesota was administered by the Minnesota Department of Health from October 18, 2021, to July 25, 2022. Advanced practice registered nurses (APRNs), physicians, physician assistants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…Health care professionals have multifaceted reasons for choosing rural practice; however, previous research has not differentiated by professional type and had relatively small sample sizes . Research exploring rural health care practice more broadly has found that the most salient factor associated with choosing rural practice is having grown up in a rural area, but that other significant factors include financial incentives, practice characteristics, and training experiences …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health care professionals have multifaceted reasons for choosing rural practice; however, previous research has not differentiated by professional type and had relatively small sample sizes . Research exploring rural health care practice more broadly has found that the most salient factor associated with choosing rural practice is having grown up in a rural area, but that other significant factors include financial incentives, practice characteristics, and training experiences …”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Research exploring rural health care practice more broadly has found that the most salient factor associated with choosing rural practice is having grown up in a rural area, but that other significant factors include financial incentives, practice characteristics, and training experiences. 5 …”
Section: Introductionmentioning
confidence: 99%